2018
DOI: 10.1136/jim-2018-000874
|View full text |Cite
|
Sign up to set email alerts
|

Statins: A New Approach to Combat Temozolomide Chemoresistance in Glioblastoma

Abstract: Patients with glioblastoma multiforme (GBM) have an average life expectancy of approximately 15 months. Recently, statins have emerged as a potential adjuvant cancer therapy due to their ability to inhibit cell proliferation and induce apoptosis in many types of cancer. The exact mechanisms that mediate the inhibitory actions of statins in cancer cells are largely unknown. The purpose of this proceeding paper is to discuss some of the known anticancer effects of statins, while focusing on GBM therapy that incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 85 publications
1
29
0
Order By: Relevance
“…Epidemiological studies have shown that the long-term consumption of statins reduces mortality rates of different types of cancer, including GBM (it is worth mentioning that in GBM, it reduces the mortality but is not statistically significant) [ 13 , 14 ]. In addition, preclinical studies have confirmed the anticancer, anti-proliferative, and anti-metastatic properties of statins in several cancers such as myeloma, leukemia, glioma, breast, and prostate cancer [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown that the long-term consumption of statins reduces mortality rates of different types of cancer, including GBM (it is worth mentioning that in GBM, it reduces the mortality but is not statistically significant) [ 13 , 14 ]. In addition, preclinical studies have confirmed the anticancer, anti-proliferative, and anti-metastatic properties of statins in several cancers such as myeloma, leukemia, glioma, breast, and prostate cancer [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased responsiveness of GBM cells to TMZ due to drug‐resistance is a major problem in the management of the GBM resulting in fatal outcome. Long‐term use of statins is associated with an increased survival rate of patients with different types of cancers , including GBM , but the underlying molecular mechanisms are unclear. Current cancer chemotherapeutic approaches have failed to achieve desired clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma Multiforme (GBM) is among the most aggressive and lethal malignancies in humans [1]; it is a devastating brain disease, which typically results in mortality within 15 months postdiagnosis due to elevated intracranial pressure and interruption of normal functioning of brain tissues [2][3][4]. In addition, GBM grows fast and can spread quickly [5][6][7].…”
Section: Introductionmentioning
confidence: 99%